Microwave Assisted Extraction of Banana Stem Waste and its Antifungal Activity against Fusarium Oxysporum - Mashuni Mashuni; muhammad Natsir; Sudirman Sudirman; Sitti Hadijah Sabarwati; Fitri Handayani Hamid; M. Jahiding (International Journal of Science Technology and Health, 2023)
Banana stem (BS) waste is obtained in large quantities in banana production. In this work, microwave extraction (MAE) from BS was used, and the solvent concentration parameters were 50%, 60%, 70%, 80%, 96% (v/v) ethanol, and 5% HCl with a sample weight of 10 g each. The influence of solvent, time, temperature, and solid: the liquid ratio was evaluated on the extraction results. Total phenolic content (TPC) and its functional performance against Fusarium oxysporum. The effect of a high ethanol concentration on BS extraction was observed because the higher ethanol solvent concentration resulted in higher extraction results and TPC. Optimal MAE conditions were determined at 200 watts for 20 minutes, with 80% ethanol showing better TPC results than other ethanol concentrations, namely 0.7171 mg g-1. The results of chemical content analysis using gas chromatography–mass spectrometry (GC-MS) of BS extract of 80% ethanol obtained phenolic compounds, carboxylic acids, aldehydes, esters, ketones, and furans. BS extract of 80% ethanol showed antifungal activity of Fusarium oxysporum with an apparent zone diameter of 9.7 mm (moderate category). It can be concluded that MAE is an efficient technique for releasing bioactive molecules from BS with TPC and antifungal applications in the agricultural industry.